2006
DOI: 10.1016/j.antiviral.2005.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of potent small molecule inhibitor of hemorrhagic fever New World arenaviruses

Abstract: Category A arenaviruses as defined by the National Institute of Allergy and Infectious Diseases (NIAID) are human pathogens that could be weaponized by bioterrorists. Many of these deadly viruses require biosafety level-4 (BSL-4) containment for all laboratory work, which limits traditional laboratory high-throughput screening (HTS) for identification of small molecule inhibitors. For those reasons, a related BSL-2 New World arenavirus, Tacaribe virus, 67-78% identical to Junín virus at the amino acid level, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
108
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 26 publications
3
108
0
Order By: Relevance
“…Studies had previously demonstrated that prior exposure of virions to ST-336 was sufficient to block subsequent infection of untreated cells (3). In order to determine the timing requirements for inhibition of cell-cell fusion, GPC-expressing cells were treated with 10 M ST-294 prior to the pH pulse, during the pH pulse, or upon return to neutrality (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies had previously demonstrated that prior exposure of virions to ST-336 was sufficient to block subsequent infection of untreated cells (3). In order to determine the timing requirements for inhibition of cell-cell fusion, GPC-expressing cells were treated with 10 M ST-294 prior to the pH pulse, during the pH pulse, or upon return to neutrality (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to develop novel effective antiarenaviral drugs and vaccines, tasks that would be facilitated by a detailed understanding of the arenavirus molecular and cell biology. Recent studies have identified small molecule inhibitors of Tacaribe virus (7) and LASV (8) cell entry, but their antiviral activity in animal models of HF arenaviruses has not been examined.…”
mentioning
confidence: 99%
“…Intervention strategies that target the steps in virus entry offer promise for effective antiviral therapeutics. Indeed, small-molecule arenavirus-specific entry inhibitors have recently been discovered (5).…”
mentioning
confidence: 99%